2011
DOI: 10.1155/2011/621414
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Human Colorectal Cancer SW1116 Cells Is Inhibited by Cytokine-Induced Killer Cells

Abstract: Previous reports have suggested that treatment with cytokine-induced killer (CIK) cells may benefit patients with various types of tumor. The aim of this study was to evaluate the antitumor effects of CIK cells against the colorectal cancer line SW1116 in vitro and in vivo. CIK cells were generated routinely from peripheral blood mononuclear cells of healthy human donors, and the number of CD3+CD56+ cells was expanded more than 1300-fold after 14-day culture. At an effector : target cell ratio of 50 : 1, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…The cytotoxic activity of CAR-T-EGFR cells was assessed by targeting the EGFR-positive human lung carcinoma cell line A549, human breast carcinoma cell line MCF7, and human cervical carcinoma cell line HeLa, as well as the EGFR-negative human ovarian cancer cell line A2780 as previously described (Zhou et al, 2013;Wang et al, 2011). The CAR-T-EGFR cells were co-cultured with A549, MCF7, HeLa or A2780 tumor cells at an effector-to-target (E : T) ratio of 5 : 1, 10 : 1, 20 : 1 and 40 : 1, respectively, for 4 h. Nonor mock-transduced cells served as controls.…”
Section: Cellular Cytotoxicity and Cytokine Assaysmentioning
confidence: 99%
“…The cytotoxic activity of CAR-T-EGFR cells was assessed by targeting the EGFR-positive human lung carcinoma cell line A549, human breast carcinoma cell line MCF7, and human cervical carcinoma cell line HeLa, as well as the EGFR-negative human ovarian cancer cell line A2780 as previously described (Zhou et al, 2013;Wang et al, 2011). The CAR-T-EGFR cells were co-cultured with A549, MCF7, HeLa or A2780 tumor cells at an effector-to-target (E : T) ratio of 5 : 1, 10 : 1, 20 : 1 and 40 : 1, respectively, for 4 h. Nonor mock-transduced cells served as controls.…”
Section: Cellular Cytotoxicity and Cytokine Assaysmentioning
confidence: 99%
“…The antitumor activity is primarily related to a high percentage of the CD3 + CD56 + subset (Ma et al, 2012;Nakano et al, 2012). The exact mechanism is still unclear, but primarily relates to the secretion of cytokines to inhibit the growth of tumor cells (Pievani et al, 2011;Wang et al, 2011;Yang et al, 2012). A large number of in vitro studies had confirmed the ability of CIK cells to kill various types of solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Adoptive cellular immunotherapy is becoming an important application for cancer therapy. In recent decades, the application of cytokine-induced killer (CIK) cells has evolved from experimental observations into early clinical studies (Morse et al, 2005;Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The present patient was treated with FK506 during CIK cell therapy to investigate how immunosuppressive drugs may affect CIK cell therapy. Certain previous studies have reported that CIK cells contain cytolytic granules that exhibit perforin and granzyme activity that are released into the extracellular space upon binding with susceptible target cells or following the cross-linking of CD3 with an anti-CD3 monoclonal antibody adhered to plastic (17)(18)(19)(20). The use of immunosuppressive drugs, such as CsA and FK506, prevented the degranulation of CIK cells that is induced by CD3-TCR stimulation; however, the drugs were unable to block the cytotoxicity that was triggered by the interaction with tumor targets.…”
Section: Discussionmentioning
confidence: 99%